El Bosque: Learnings and Experiences from the FirstPhase of Implementation of the innovation habitat(2021-2022) Universidad Nacional - Vargas Herencia, Karla (2025)
The El Bosque project emerged in response to the health crisis that affected the artistic and cultural sector of Costa Rica, due to SARS-CoV-2. This article describes the implementation of the first phase of the El Bosque innovation habitat, during the years 2021 and 2022. Its fundamental purpose was to develop a value proposition for knowledge exchange to boost the economic recovery of the artistic sector, actively integrating students from the National University (UNA). Through an open innovative approach, El Bosque established strategic alliances with various innovative environments and experts across multiple disciplines. This work highlights the characteristics and uniqueness of the project, which was reflected in the offering of an advisory program and the conduct of public events designed to support individuals with entrepreneurial ventures. Through a reflective analysis of the processes and achievements, the article emphasizes the learnings, experiences, and contributions of El Bosque in promoting innovation and encouraging continuous improvement for the sustainability of the ventures that participated in the first phase.